The Concept of Cyber Resilience in the European Union Law - Szpor, Grażyna Maria (Review of European and Comparative Law, 2026)
The legal framework for digital transformation in the European Union is being supplemented by further acts that should enable it to meet current challenges while respecting EU values and principles redefined in the context of cyberspace. An example is Regulation 2024/2847 on horizontal cybersecurity requirements (Cyber Resilience Act). It does not define the term used in the abbreviated title. The relationship between cyber resilience and cybersecurity, and their place within the conceptual framework of digital transformation, remains unclear. This article aims to identify terminological issues that require doctrinal agreement, to consider the possibilities for achieving this, and to propose solutions. An analysis of how the purpose of the act is reflected in its title, definitions, scope, structure and initial stage of application was carried out using a legal-dogmatic method, including a systemic approach. It confirmed the verified hypotheses about the underestimation of the importance of short titles of acts in EU legislative processes and the untapped potential of the concept of cyber resilience in increasing the consistency and transparency of law, which is essential for its effectiveness. The result is a proposal to amend EU legislative drafting rules on short titles and to adopt a general definition of cyber resilience as a higher-order concept capable of integrating scattered sectoral regulations and performing an organizing function for digital transformation processes in legal doctrine.